Genetic variants of uncertain significance: How to match scientific rigour and standard of proof in sudden cardiac death?. (July 2020) - Grassi, Simone; Campuzano, Oscar; Coll, Mònica; Brión, María; Arena, Vincenzo; Iglesias, Anna; Carracedo, Ángel; Brugada, Ramon; Oliva, Antonio
Highlights: An obese 7-year-old girl in healthy state was found dead in her bed. We found a myocardial bridging of the left anterior descending coronary artery. Molecular autopsy found variants of unknown significance. As in several cases of pediatric sudden deaths, we only found uncertain causes of death. There are no forensic guidelines for cases of variants of unknown significance. Abstract: In many SCD cases, in particular in pediatric age, autopsy can be completely negative and then a post-mortem genetic testing (molecular autopsy) is indicated. In NGS era finding new/rare variants is extremely frequent and, when only variants of unknown significance are found, molecular autopsy fails to find a cause of death. We describe the emblematic case of the sudden death of a 7-year-old girl. We performed a full-body micro-CT analysis, an accurate autopsy, a serum tryptase test and toxicological tests. Since the only macroscopic abnormality we found was a myocardial bridging (length: 1, 1 cm, thickness: 0, 5 cm) of the left anterior descending coronary artery, a molecular autopsy has been performed. NGS analysis on victim DNA detected rare variants in DPP6, MYH7, SCN2B and NOTCH1 and segregation analysis was then achieved. On the basis of ACMG/AMP (clinical) guidelines, all the found variants were classified as of unknown significance. In other words, both the macroscopic and genetic anomalies we found were of uncertain significance and then the autopsy failed to find the cause of the death. Our case raises three main discussion points: (a) economical, ethical and legal limitations of genetic investigation; (b) risk that genetic testing does not succeed in finding a certain cause of the death; (c) absence of specific guidelines to face the problem of VUS in forensic cases.